Variability Studies for Seed and Seedling Traits in Calophyllum Inophyllum (L.) at South India - Kumaran, Palani (Indian Journal of Hill Farming, 2015)
The present investigation was carried out at Forest College and Research Institute, Mettupalayam, Tamilnadu to identify the best half sibs of Calophyllum inophyllum across its natural distribution of south India for further collection of seeds for afforestation or breeding purpose. The seeds were collected from different climatic zones of south India. Seeds were measured for its length, width, Pod length, Width and then sown in nursery to study the variation in germination and initial growth parameters viz., germination percent, germination value, peak value, mean daily germination of seedlings. Seeds collected from Western Ghats of Karnataka were superior compared to seeds from other parts in all the traits considered for the study. These seed sources can be further screened for tree improvement traits considering their immense value in yielding bio diesel.